NILAI GIZI DAN SIFAT ORGANOLEPTIK YOGHURT UMBI GEMBILI DENGAN PENAMBAHAN SARI BUAH NAGA MERAH - Wida Aulia (2020)
Cancer prevalence in Indonesia in 2013-2018 has increased to 1.8%. The incidence of cancer can be prevented by consuming foods that contain antioxidants because it can prevent oxidative stress and cancer. One food that contains antioxidants is red dragon fruit juice and yogurt. This study aims to determine the nutritional content and acceptability of consumers organoleptically and to determine the selected formula of sweet tuber synbiotic yogurt with the addition of red dragon fruit juice. The research design used is experimental. Organoleptic test was analyzed using the Kruskal Wallis test and continued with the Mann-Whitney test. Kruskal Wallis test results showed the addition of red dragon fruit juice had a significant effect (p <0.05) on the hedonic test of taste parameters (p = 0.001) and texture (p = 0.001). The selected formula was determined using the Bayes method based on the organoleptic test value with the result of the selected formula being F2 sinbiotic yogurt with the addition of 15% red dragon fruit juice. Sinbiotic yogurt F2 contains 87.23% water content, 0.83% ash content, 1.75% protein content, 0.97% fat content, and 9.2% carbohydrate content.